Analysis of Employee Performance: A Case Study in Port Corporation - Nazwirman Nazwirman (Jurnal Organisasi dan Manajemen, 2019)
The purpose of this study is to analyze the effect of compensation, work environment and work discipline on employee performance at the Indonesia Port Corporation. This is important for managers in making decisions in the company, especially matters relating to human resources. The population of this research was all the employees of the human resources division. The sampling technique used was saturated sampling, where data was collected using a survey method, namely a questionnaire. The results showed that all variables had a positive and significant effect on employee performance, both partially and simultaneously. The results of this study confirm that port management companies must pay attention to compensation, work environment and work discipline if it expects superior performance from its employees.